Substantive signifiers? Ethnic and religious identifications among second-generation immigrants in the Netherlands. Issue 5 (2nd September 2016) - Slootman, Marieke
Abstract : In the context of increasingly 'culturalised' discourses on immigrant integration in Europe, this article aims to contribute to a de-essentialised understanding of ethnic and religious identity. Based on the analysis of quantitative data, it reveals the multifarious relationship between identification and culture among second-generation Turkish and Moroccan Dutch in the Netherlands. Some instances of self-identification with nominal labels ('Turkish' and 'Muslim') appear to go hand in hand with stronger sociocultural orientations in daily life and are more substantive; others ('Moroccan') do not. These findings point to different social mechanisms at work in shaping identifications with certain identity labels and once more illustrate that ethnic and religious identifications do not necessarily reflect cultural 'otherness'.